ACCOUNTING REDISCOVERED. - Littleton, A. C. (The Accounting Review, 1958)
Abstract Economists have long realized that over the years much of the impulse to write anew about economic principles originated in the mood of the times. This awareness of the relativity of economic thought to its time of appearance has produced a special literature history of economic doctrine. The focus of interest in accounting however has for centuries been turned toward its usefulness in practical affairs. Its evolutionary development has been strongly influenced by that fact. Its service from the beginning has been that of expressing and systematically organizing the data of economic acts and business decisions stated in quantitative terms. The acceptability of that kind of service has been so positive that the literature has been concerned with improved technology and the professionalization of independent auditing. Although the recording methodology which developed into accounting is usually called double-entry bookkeeping, a much more descriptive name would be "Italian capital-income accounting." That phrase carries a deeper significance than duality. For dual entry and equality of trial balance totals are very superficial aspects of accounting technology.